Manly Militants, Cohesive Communities, and Defiant Domestics: Writing about Immigrants in Canadian Historical Scholarship - Iacovetta, Franca (Labour / Le Travail, 1995)
A chapter of the book "Labour/Le Travail" is presented. It explores the historical works on immigrants in Canada that offer significant contributions to immigrant history in the country. It highlights the emergence of new approaches that promote new ways of writing about immigrants. It highlights the belief of scholars that race-ethnicity is a significant category of analysis as well as issues on the popularity of the class-gender-race/ethnicity analytical framework.
Keywords: Canada; Ethnicity; IMMIGRANTS -- History; LABOUR/LE Travail (Book); SCHOLARS

Such Hardworking People: Italian Immigrants in Postwar Toronto - Iacovetta, Franca (McGill-Queen's studies in ethnic history, 1993)
During the last century, 26 million Italian women, men, and children have traded an uncertain future in Italy for the prospect of a better life elsewhere. Canada has long been home to Italian immigrants, but in the years just after the Second World War they began to arrive in multitudes. Toronto emerged as the most popular Canadian destination and now, with more than 400,000 residents of Italian heritage, has one of the largest Italian populations outside Italy. Franca Iacovetta describes the working-class experiences of those who came to Toronto from southern Italy between 1946 and 1965, focusing on the relations between newly arrived immigrant workers and their families." "The Italians who came to Toronto before 1965 were predominantly young, healthy women and men eager to secure jobs and prepared to make sacrifices in order to secure a more comfortable life for themselves and their children. Franca Iacovetta examines the changes many of them had to face during the transition from peasant worker in an under-developed, rural economy to wage-earner in an urban, industrial society." "Although both women and men had to struggle and were exploited, Iacovetta shows that they found innovative ways to recreate cherished rituals and customs from their homeland and to derive a sense of dignity and honour from the labours they performed." "Such Hardworking People is informed by a feminist analysis. Iacovetta shows that for both sexes work patterns and experiences, as well as self-perceptions, were influenced by domestic responsibilities and gender relations within the household and by the labour market, employer strategies, and kin-linked networks of support. In addition to conducting numerous interviews with some of the immigrants, she has drawn on recent scholarship in immigration, family, labour studies, oral history, and women's history. --Publisher's description
Keywords: Canadiens d'origine italienne Ontario Toronto Conditions sociales; Foreign workers, Italian; Foreign workers, Italian Ontario Toronto; Immigrants Ontario Toronto Conditions sociales; Immigrants Ontario Toronto Social conditions; Immigrants Social conditions; Italian Canadians Ontario Toronto Social conditions; Italians Ontario Toronto Social conditions; Italians Social conditions; Italiens Ontario Toronto Conditions sociales; Ontario Toronto; Travailleurs étrangers italiens Ontario Toronto

Women, Work, and Protest in the Italian Diaspora: An International Research Agenda - Gabaccia, Donna; Iacovetta, Franca (Labour / Le Travail, 1998)
Interrogates the currents of scholarly inquiry into the Italian emigration of the 19th and 20th centuries. Argues for a woman-centred, gendered, and proletarian history of this diaspora, and suggests new areas of investigation.

Italian Radicals in Canada: A Note on Sources in Italy - Iacovetta, Franca; Ventresca, Robert (Labour / Le Travail, 1996)
Discusses and provides examples of documentation of Italian radicals in Canada at the Casellario Politico Centrale (Rome), the files of which were extensive during the Fascist dictatorship in Italy (1922-43) since the regime wanted to identify and monitor its opponents. Argues that these materials may be used to write the history of the Italian left/anti-Fascism in Canada as well as contributing to studies of Canadian labour/immigration history and the international anti-fascist movement.
Keywords: Canada; EMIGRATION & immigration; FILES (Records); History; IACOVETTA, Franca; LABOUR/LE Travail (Book); Labor; RADICALS; VENTRESCA, Robert

Women's History, Gender History and Debating Dichotomies - Iacovetta, Franca; Kealey, Linda (Left History: An Interdisciplinary Journal of Historical Inquiry and Debate, 1996)
Joan Sangster's "Beyond Dichotomies" (left history, 3.1, Spring/Summer 1995) is a polemic on the relationship between women's history and gender history. As such, it tends to bring out issues and highlight debates but, at the same time, it sometimes inevitably simplifies and potentially misrepresents in order to address important points. As friends and colleagues, we would like to take issue with some of the assertions and suggestions made in Sangster's piece. We think it is important to debate these issues and we hope to make a contribution. Such issues are central in feminist historical debates internationally and, while individuals who write Canadian women's history and gender history have clearly borrowed from the intemational literature, there has been no sustained Canadian "debate," at least not in print. --Introduction

Gender Conflicts: New Essays in Women's History - Iacovetta, Franca; Valverde, Mariana (Social history of Canada, 1993)
In the early 1970s, when women's history began to claim attention as an emerging discipline in North American universities, it was dominated by a middle-class Anglo-Saxon bias. Today the field is much more diverse, a development reflected in the scope of this volume. Rather than documenting the experiences of women solely in a framework of gender analysis, its authors recognize the interaction of race, class, and gender as central in shaping women's lives, and men's. These essays represent an exciting breakthrough in women's studies, expanding the borders of the discipline while breaking down barriers between mainstream and women's history. --Publisher's description. Contents: When the mother of the race is free': Race, reproduction, and sexuality in first-wave feminism / Mariana Valverde -- Maidenly girls' or 'designing women'? The crime of seduction in turn-of-the-century Ontario / Karen Dubinsky -- The 'hallelujah lasses': Working-class women in the Salvation Army in English Canada, 1882-92 / Lynne Marks -- The alchemy of politicization: Socialist women and the early Canadian left / Janice Newton -- Wounded womanhood and dead men: Chivalry and the trials of Clara Ford and Carrie Davies / Carolyn Strange -- Class, ethnicity, and gender in the Eaton strikes of 1912 and 1934 / Ruth A. Frager -- 'Feminine trifles of vast importance': Writing gender into the history of consumption / Cynthia Wright -- Making 'new Canadians': Social workers, women, and the reshaping of immigrant families / Franco Iacovetta.

A Nation of Immigrants: Women, Workers, and Communities in Canadian History, 1840s-1960s - Iacovetta, Franca; Draper, Paula; Ventresca, Robert (Canada 150 Collection, 1998)
This collection brings together a wide array of writings on Canadian immigrant history, including many highly regarded, influential essays. Though most of the chapters have been previously published, the editors have also commissioned original contributions on understudied topics in the field. The readings highlight the social history of immigrants, their pre-migration traditions as well as migration strategies and Canadian experiences, their work and family worlds, and their political, cultural, and community lives. They explore the public display of ethno-religious rituals, race riots, and union protests; the quasi-private worlds of all-male boarding-houses and of female domestics toiling in isolated workplaces; and the intrusive power that government and even well-intentioned social reformers have wielded over immigrants deemed dangerous or otherwise in need of supervision.Organized partly chronologically and largely by theme, the topical sections will offer students a glimpse into Canada's complex immigrant past. In order to facilitate classroom discussion, each section contains an introduction that contextualizes the readings and raises some questions for debate. A Nation of Immigrants will be useful both in specialized courses in Canadian immigration history and in courses on broader themes in Canadian history. --Publisher's description. Contents: The Irish in nineteenth-century Canada: class, culture, and conflict -- American Blacks in nineteenth-century Ontario: challenging the stereotypes -- Settling the Canadian West: the 'exotic' continentals -- 'Women's work': paid labour, community-building, and protest -- Men without women: 'bachelor' workers and gendered identities -- Demanding rights, organizing for change: militants and radicals -- Encountering the 'other': society and state responses, 1900s-1930s -- Regulating minorities in 'hot' and 'cold' war contexts, 1939-1960s.

Editor's Note = Note du directeur [39, Spring 1997] - Iacovetta, Franca; Quinlan, Michael; Kealey, Gregory S. (Labour/Le Travail, 1997)
A letter to the editor is presented in response to the article "Immigration and Labour: Australia and Canada Compared" published in "Labour/Le Travail."
Keywords: LETTERS to the editor; Labor